Neurological Insights Into Disruptive Mood Dysregulation Disorder: A Case Of Demyelination - Dhankar, Abhinav; Ambawata, Priya; Swarup, Praneta; Kumar, Abhinit; Kumar, Kunal; Nayar, Nikhil; Bhargava, Siddharth (Journal of Neonatal Surgery, 2025)
Disruptive Mood Dysregulation Disorder (DMDD) is a pediatric mood disorder marked by persistent irritability and severe temper outbursts disproportionate to the situation, typically emerging before age 10. It is differentiated from pediatric bipolar disorder, preventing misdiagnosis and inappropriate treatment. DMDD involves recurrent behavioral dyscontrol disrupting daily functioning and shares symptoms with conditions like oppositional defiant disorder (ODD) and ADHD. However, its defining features include pervasive mood dysregulation and prolonged emotional reactions, highlighting the importance of recognizing irritability as a core symptom in children. Here we present a case of a 10 year old female, Hindu from Greater Noida, studying in 2 nd class in a private school with no past history of head trauma or developmental delay was brought to the Psychiatry OPD by parents with complaints of crying spells, unprovoked persistent irritable behavior grossly out of proportion to the situation associated with recurrent outbursts/tantrums 3-4 days/week along with physical aggression towards people in school as well as at home with inter episode mood being irritable for most of the day and reduced scholastic performance since past 1 year which has increased since 6 months. On MSE, patient was kempt, tidy, restless, partially cooperative, crying, reduced rate and tone of speech, irritable affect, easy distractibility, reduced concentration, average intelligence and grade 1 insight. Patient qualifies the criteria of DMDD. After treatment with Escitalopram 5 mg and Risperidone 0.5 mg. Patients’ irritability, crying spells and behavioral symptoms have improved. Patient is currently maintaining well. Despite progress in understanding Disruptive Mood Dysregulation Disorder (DMDD), several gaps remain, including the lack of longitudinal data on its development and limited evidence on pharmacological treatments. Cross-cultural applicability and neurobiological mechanisms, particularly in amygdala-prefrontal circuitry, need further exploration. Additionally, DMDD’s comorbidity with ADHD, anxiety, and ODD complicates diagnosis. Future research should address these areas to improve diagnosis, treatment, and outcomes for affected children.